2022
DOI: 10.1007/s11356-022-19324-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males

Abstract: Current experiment was planned to investigate the deleterious effects of the graded dose of a atoxin B1 (AFB1) on White Leghorn Male Birds. For this purpose, 100 birds of 8 week age were divided into 4 equal groups and reared on feed contaminated with different doses of AFB1 for 10 weeks. Group A was kept as a control group and was fed with normal toxin free diet, group B, C, and D were offered feed containing 100 ppb, 200 ppb, and 400 ppb of AFB1 respectively. The birds were euthanized at the 4 th and 10 th w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…AFB 1 is a mycotoxin that can contaminate agricultural products and accumulate in livestock and poultry through the enrichment in the food chain, causing serious food safety problems . Our previous study found that AFB 1 decreased testis coefficients, and damaged testicular morphology of mice. , One of the main functions of the testis is to synthesize T. Reduced T biosynthesis caused by AFB 1 is the main factor that induces reproductive dysfunction and male infertility; , however, the precise mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AFB 1 is a mycotoxin that can contaminate agricultural products and accumulate in livestock and poultry through the enrichment in the food chain, causing serious food safety problems . Our previous study found that AFB 1 decreased testis coefficients, and damaged testicular morphology of mice. , One of the main functions of the testis is to synthesize T. Reduced T biosynthesis caused by AFB 1 is the main factor that induces reproductive dysfunction and male infertility; , however, the precise mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…8 Testis is the main target organ of AFB 1 attack, and its exposure can lead to testicular structural damage and testosterone (T) biosynthesis inhibition. 9 T is the most important male hormone synthesized in the testis, responsible for maintaining spermatogenesis and ensuring male reproductive function, the decreased T delays sexual maturation, and reduces semen quality and reproductive capacity. 10 The biosynthesis of T is a process in steroidogenesis that occurs in the Leydig cells (LCs), closely related to luteinizing hormone (LH) and follicle-stimulating hormone (FSH), which are synthesized by the pituitary gland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gross and microscopic changes in the aflatoxin groups were more pronounced with the increase in the level of the toxin present in the feed. Decreases in testicular size and volume and reproductive hormones like LH, prolactin, and testosterone were evident with increased levels of AFs in animal feed ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AFB 1 exposure decreased spermatogenesis in mice by inducing oxidative stress, decreasing mitochondrial content, and upregulating the pro-apoptotic Bax, p53 and Caspase 3 ( Yasin, Mazdak & Mino, 2018 ). AFB 1 also induced testicular damage and testicular dysfunction in Dorper rams ( Lin et al, 2022 ), and impaired spermatogenesis in white leghorn cockerels ( Ashraf et al, 2022 ). Exposure to low concentrations of AFB 1 for several hours can decrease spermatozoa motility, hyperpolarize mitochondrial membranes, and increase DNA fragmentation ( Komsky-Elbaz, Saktsier & Roth, 2018 ).…”
Section: Afb 1 -Induced Toxicitymentioning
confidence: 99%